How collective is collective efficacy?: the importance of consensus in judgments about community cohesion and willingness to intervene - Brunton-Smith, Ian (Criminology, 2018)
Existing studies have generally measured collective efficacy by combining survey respondents’ ratings of their local area into an overall summary for each neighborhood. Naturally, this approach results in a substantive focus on the variation in average levels of collective efficacy between neighborhoods. In this article, we focus on the variation in consensus of collective efficacy judgments. To account for differential consensus among neighborhoods, we use a mixed‐effects location‐scale model, with variability in the consensus of judgments treated as an additional neighborhood‐level random effect. Our results show that neighborhoods in London differ, not just in their average levels of collective efficacy but also in the extent to which residents agree with one another in their assessments. In accord with findings for U.S. cities, our results show that consensus in collective efficacy assessments is affected by the ethnic composition of neighborhoods. Additionally, we show that heterogeneity in collective efficacy assessments is consequential, with higher levels of criminal victimization, worry about crime, and risk avoidance behavior in areas where collective efficacy consensus is low.